Tax Evasion on a Social Network - Duccio Gamannossi degl'Innocenti; Matthew D. Rablen (Center for Economic Studies and ifo Institute (CESifo), 2018)
We relate tax evasion behavior to a substantial literature on self and social comparison in judgements. Tax payers engage in tax evasion as a means to boost their expected consumption relative to others in their “local” social network, and relative to past consumption. The unique Nash equilibrium of the model relates optimal evasion to a (Bonacich) measure of network centrality: more central taxpayers evade more. The indirect revenue effects from auditing are shown to be ordinally equivalent to a related Bonacich centrality. We generate networks corresponding closely to the observed structure of social networks observed empirically. In particular, our networks contain celebrity taxpayers, whose consumption is widely observed, and who are systematically of higher wealth. In this context we show that, if the tax authority can observe the social network, it is able to raise its audit revenue by around six percent.
Keywords: H26; D85; K42; 330; tax evasion; social networks; network centrality; optimal auditing; social comparison; self comparison; habit; indirect effects; relative consumption